Colour and Quality of Strawberry fruit (Fragaria x ananassa Duch.) at Different Levels of Maturity - Ni Made Defy Janurianti; I Made Supartha Utama; Ida Bagus Wayan Gunam (Warmadewa University Press, 2021)
Strawberry fruit has five levels of maturity in terms of the color of the strawberry fruit. One of the important factors that affect the fruit's resistance from mechanical damage is the level of fruit maturity. At different levels of ripeness, strawberries have different nutritional content. The strawberries used are obtained from strawberry farmers in Pancasari Village, Tabanan Regency. The level of fruit maturity analyzed was divided into five stages, namely 0, 25%, 50%, 75%, and 100% of the red fruit. Based on the ANOVA variety results, the parameters of color, texture, pH, total acid content, total acid content, vitamin C content, and anthocyanin levels of strawberries at different levels of maturity showed very significant differences (P <0.01). Strawberry fruit at the optimal level of maturity obtained the value of L *, namely 18.45, a *, namely 67.04, b *, namely 20.86, texture of 7.46 N, pH of 3.36, total acid of 2.09 (meq NaOH / g), total dissolved solids was 6.40 oBrix, vitamin C levels were 66.24 mg / 100, and anthocyanin levels were 329.07 (mg PGN / 100 g).